1932
DOI: 10.1002/ajpa.1330170212
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory adaptation in the Indian natives of the peruvian andes. Studies at high altitude

Abstract: FIVE FI(tUEE6Among the physiological adjustments to a low barometric pressure an increase in ventilation is perhaps one of the most important. In consequence we may suppose that the native of high altitude possesses a respiratory mechanism adapted for a better ventilation and for an efficient interchange of respiratory gases. But, curiously enough, this logical supposition has not been adequately investigated, and throughout the extensive literature related to high altitude it is only briefly mentioned, or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
2

Year Published

1933
1933
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(44 citation statements)
references
References 13 publications
2
40
0
2
Order By: Relevance
“…Theoretically, we may conceive of cases in which, without the development of emphysema, the alveolar space is encroached upon so severely by the presence of pathological tissue or fluid that a considerable reduction in the amount of air results. One of us (4) has shown that natives at high altitudes, fully adapted to the low oxygen tension, exhibit large emphysematous chests. Although no measurements have been made, we may infer that their lungs would show large mid capac- …”
Section: Prediction Of the Normal Capacity Of The Lungsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, we may conceive of cases in which, without the development of emphysema, the alveolar space is encroached upon so severely by the presence of pathological tissue or fluid that a considerable reduction in the amount of air results. One of us (4) has shown that natives at high altitudes, fully adapted to the low oxygen tension, exhibit large emphysematous chests. Although no measurements have been made, we may infer that their lungs would show large mid capac- …”
Section: Prediction Of the Normal Capacity Of The Lungsmentioning
confidence: 99%
“…Deficient expansion tends to be accompanied by a higher percentage of the residual air in relation to the total capacity. 4. There is a relationship between the shape of the chest and the capacity of the lungs.…”
mentioning
confidence: 99%
“…The indigenous populations of the South American Andean plateau show morphological and physiological adaptations to hypoxic stress (Rupert and Hochachka, 2001;Beall, 2007a). They have a larger thorax (Hurtado, 1932), higher lung capacity (Frisancho, 1969), higher lung diffusion rate (Jones et al, 1992), and higher hemoglobin levels than lowlanders (Faura et al, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…According to the current interpretation of the average difference, a figure that approaches 2 suggests a doubtful iden- (1930) when handled in the same way yield a figure of 162.2. Also, Hooton's data on Madisonville (1920), which Neumann (1941a) Gillin, 1911;Hurtado, 1932) ; the recent Pueblos average 164 cm. (Hrdlicka, 1935 …”
mentioning
confidence: 97%